Promoting the Transformation of Old Industrial Bases Through Energy Revolution - Huang Qili (《中国工程科学》杂志社, 2021)
The old industrial bases in China are facing various problems and challenges owing to the contradiction between the institutional mechanism and economic structure, and energy revolution is an important support for the transformation of these old industrial bases. In this study, the basic characteristics and development status of the old industrial bases in Northeast China and Shanxi are elaborated, the key problems regarding energy transformation in these places are analyzed. Moreover, an energy transition strategy is proposed for the old industrial bases, and strategic measures and policy suggestions are offered. Through quantitative analysis and strategic study, we expound the connotation and strategic positioning of energy revolution in the old industrial bases and propose the strategic goals for the transformation of the old industrial bases by 2035 and 2050. To transform and upgrade the energy industry in the old industrial bases and optimize the energy production and consumption modes, the following measures are proposed: constructing a special energy economic zone within Shanxi, Eastern Inner Mongolia, and Northeast China; encouraging shale oil development; promoting the comprehensive utilization of abandoned oil and gas reservoirs and abandoned mines; supporting the transformation of resource-dependent areas; promoting diversified utilization of fossil energy resources; building a demonstration base for diversified utilization of renewable energy; and establishing a talent incentive policy mechanism.